STUDI KOMPARATIF PENGGUNAAN LAMPU PADA KEGIATAN PENANGKAPAN IKAN DI PERAIRAN MARTAPURA - Siti Aminah; Ahmadi Ahmadi (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2017)
This study aims to find out the comparison of constant use of lights and flashing lights in fishing activities by means of fishing gear done in Martapura swamp waters, Banjar Regency, South Kalimantan Province. From the results obtained in the results obtained that the fish like a constant light more in the likes of fish in comparison to thetype of flashing lights.